Association Between Vitamin D, Reproductive Hormones and Sperm Parameters in Infertile Male Subjects - Rehman, Rehana; Lalani, Salima; Baig, Mukhtiar; Nizami, Iman; Rana, Zohaib; Gazzaz, Zohair Jamil (Frontiers in Endocrinology, 2018)
Background: The prevalence of infertility and vitamin D deficiency is common in Pakistan. Therefore, our study aims were to assess and compare Vitamin D; 25-hydroxyvitamin (25OHD) and reproductive hormone levels in male fertile and infertile subjects with normal and abnormal sperm parameters. Furthermore, the study is aimed to explore the association of 25OHD levels with these sperm parameters in a selected population of Karachi, Pakistan. Methods: The cross-sectional study was carried out from August 2016 till December 2017, 313 study subjects were recruited from an Infertile Clinic from Islamabad, Pakistan, and the general population. First, we took the couples’ history of parenting and then carried out a semen analysis and infertile and fertile male subjects were then subgrouped into ‘normal’ and ‘altered sperm parameter/s.’ Forward linear regression was done for selection of 25OHD as a significant predictor of sperm parameters. Results: The median values of the total count, motility, morphology as well as serum 25OHD were significantly higher in the group with ‘normal’ (186) as compared to subjects (127) in ‘abnormal sperm parameters’ group. The 25OHD levels were significantly high in males with ‘normal sperm parameters’; 80.90 ± 23.33 nmol/L vs. “altered sperm parameter/s’, 64.68 ± 24.21 nmol/L (mean ± SD) with p < 0.001. Serum testosterone level had a significant positive correlation with 25OHD while LH had a significant negative correlation with 25OHD (p<.001), and FSH level had a non-significant negative correlation with 25OHD. Results of regression model showed one unit increase of motility would give 0.15-unit positive significant impact on 25OHD; 20% variation in 25OHD was explained by the total count, motility, and morphology, while the model was adjusted for BMI. Conclusion: The impact of 25OHD levels on sperm parameters can be emphasized on the basis of detection of its high serum levels in ‘normal’ subjects in both fertile as well as infertile males in comparison to subjects that had altered sperm parameters; total sperm count, motility, and normal morphology. The considerably positive association between 25OHD, testosterone, total count, motility, and morphology further accentuates its impact on normal spermatogenesis and the male reproductive functions required for acquiring fertility.